1) 11х^2-6x-27=8x^2-6x
11x^2-6x-27-8x^2+6x=0
3x^2-27=0
3x^2=27
x^2=27/3
x^2=9
x=3
2) 26+5y-0,5y^2=2,5y^2+26
26+5y-0,5y^2-2,5y^2-26=0
5y-3y^2=0
y(5-3y)=0
y=0 5-3y=0
3y=5
y= 5/3
3)-7x^2+13x+9=-19+13x
-7x^2 +13x +9 +19 -13x=0
-7x^2 +28 =0
7x^2=28
x^2 = 4
x=2
4) 21z+11=11+17z-5z^2
21z+11-11-17z^2=0
21z-17z^2=0
z(21-17z)=0
z=0 17z=21
я= 21/17
5)(x-5)^2+ 4x = 25
x^2-10+25 +4x =25
x^2 +4x = 10
x (x+4)=10
x=10 x+4 =10
x=6
1) 11х^2-6x-27=8x^2-6x
11x^2-6x-27-8x^2+6x=0
3x^2-27=0
3x^2=27
x^2=27/3
x^2=9
x=3
2) 26+5y-0,5y^2=2,5y^2+26
26+5y-0,5y^2-2,5y^2-26=0
5y-3y^2=0
y(5-3y)=0
y=0 5-3y=0
3y=5
y= 5/3
3)-7x^2+13x+9=-19+13x
-7x^2 +13x +9 +19 -13x=0
-7x^2 +28 =0
7x^2=28
x^2 = 4
x=2
4) 21z+11=11+17z-5z^2
21z+11-11-17z^2=0
21z-17z^2=0
z(21-17z)=0
z=0 17z=21
я= 21/17
5)(x-5)^2+ 4x = 25
x^2-10+25 +4x =25
x^2 +4x = 10
x (x+4)=10
x=10 x+4 =10
x=6
x/(2 - x) - 3/4 * √(x/(2 - x)) ≥ 1/4
ОДЗ x/(2 - x) ≥ 0
x/(x - 2) ≤ 0
[0] (2)
х∈ [0 2)
x/(2 - x) - 2 *3/8 * √(x/(2 - x)) + 9/64 - 9/64 ≥ 1/4
√(x/(2 - x)) = t >=0
t² - 2 * 3/8 * t + (3/8)² ≥ 16/64 + 9/64
(t - 3/8)² - (5/8)² ≥ 0
(t - 3/8 - 5/8)(t - 3/8 + 5/8) ≥ 0
(t - 1)(t + 1/4) ≥ 0
вторая скобка больше 0 всегда - отбрасываем ее
t - 1 ≥ 0
√(x/(2 - x)) ≥ 1
x/(2-x) - (2-x)/(2-x) ≥ 0
(x - 2 + x)/(2 - x) ≥ 0
(2x - 2)/(x - 2) ≤ 0
[1] (2)
х∈[1 2)
пересекаем с ОДЗ
x∈[1 2)